POLA PENYEBARAN POHON GOFASA (Vitex cofassus Reinw. Ex Blume) DI KAWASAN TAHURA PALU - Adrianto, Adrianto; Umar, Husain; Toknok, Bau (Jurnal Warta Rimba, 2015)
Vitex cofassus Reinw. Ex. Blume is a importantplants, and in local name popularly known as Bitti. This species grow widely in great forest garden of Palu area. The research was conducted at great forest garden, Palu, Central Sulawesi from May to July 2013. This study was aimed to determine the distribution pattern and density of Vitex cofassus Reinw. Ex. Blume trees. This study was using a line plots method and plant samples recorded by using discontinue technique.Plots with size 20 m x 20 m were made in each line.The study employed analysis of Morisita index. The results showed that based on the Morisita index value 1,04-1,05, the distribution pattern of Vitex cofassus Reinw. Ex. Blume trees wasfocused in one group with density value between 28-29 trees per hectare. Keywords: Distribution pattern, Vitex cofassus Reinw. Ex. Blume, Great Forest Garden, Tahura.